2014
DOI: 10.1213/ane.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

Is Video Laryngoscope-Assisted Flexible Tracheoscope Intubation Feasible for Patients with Predicted Difficult Airway? A Prospective, Randomized Clinical Trial

Abstract: Flexible tracheoscope-assisted video laryngoscopic intubation is a feasible alternative to video laryngoscope only intubation in patients with predicted difficult airways. A flexible tracheoscope used in combination with video laryngoscope may also further increase the success rate of intubation in select patients with a proven difficult airway, particularly when in-line stabilization is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 27 publications
1
32
0
2
Order By: Relevance
“…A combined approach must be chosen . These combinations of McIntosch + Fob [15], VLS + FOB [13][14][15][16], AirTraq + FOB [17], VLS + Bonfils [14][15][16][17][18], McIntosch + Optical Stylet [19] have been reported to be successful under difficult conditions, which confirms that all stages of intubation should be performed under vision. The intervention must select one of the combined approaches that has the greatest likelihood of success, is the most secure, and is easy to perform, facilitating secure ventilation in the event of failure (face mask or extraglottic tools ) and allowing patient to awaken.…”
Section: Not Intubated and Non-ventilatedmentioning
confidence: 80%
See 1 more Smart Citation
“…A combined approach must be chosen . These combinations of McIntosch + Fob [15], VLS + FOB [13][14][15][16], AirTraq + FOB [17], VLS + Bonfils [14][15][16][17][18], McIntosch + Optical Stylet [19] have been reported to be successful under difficult conditions, which confirms that all stages of intubation should be performed under vision. The intervention must select one of the combined approaches that has the greatest likelihood of success, is the most secure, and is easy to perform, facilitating secure ventilation in the event of failure (face mask or extraglottic tools ) and allowing patient to awaken.…”
Section: Not Intubated and Non-ventilatedmentioning
confidence: 80%
“…have success rates of 97-98% [10][11][12]. A combined approach using tools that display the glottic region and instruments that also display the trachea allows the tube to be introduced and placed under vision and resolves the majority of difficult cases [13][14][15][16].…”
Section: Not Intubated and Non-ventilatedmentioning
confidence: 99%
“…[15][16][17] Some reports have suggested that tracheostomy is not routinely necessary and should not be used as the primary procedure for control of the airway in patients with Ludwig angina or infections of the deep spaces. 11,12 Video laryngoscopic intubation, being a relatively new technique, has been widely used in the management of difficult airways in recent years, 17,18 as it allows visualisation of the larynx without alignment of the oropharyngeal and laryngeal axis. It also provides excellent exposure and an improved laryngeal view with reduced intubation time, and has been used recently in the management of the airway in deep neck infections and Ludwig angina.…”
Section: Discussionmentioning
confidence: 99%
“…In operators with limited experience with flexible fiberoptic devices, a combined technique using a flexible fiberoptic device with a laryngoscope can be helpful. 103 Human factors: training, algorithms, and bundles…”
Section: Device Selectionmentioning
confidence: 99%